2006
DOI: 10.3354/meps324281
|View full text |Cite
|
Sign up to set email alerts
|

Sex ratios of juvenile loggerhead sea turtles Caretta caretta in the Mediterranean Sea

Abstract: Species with environmental sex determination may show sex ratios that differ from 1:1; therefore, sex ratio is an important variable when studying the population dynamics of these species. For instance, when estimating population size and productivity, sex ratio would be a required parameter. For endangered species, such as sea turtles, this is particularly important in order to understand the possible effects of human impacts and conservation measures. Unfortunately, only adult sea turtles show evident extern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 12 publications
(13 reference statements)
3
36
0
1
Order By: Relevance
“…The second important area for loggerhead hatchlings appears to be the Ionian-south Adriatic. Accordingly, turtles of the size range (<10 cm), corresponding approximately to the age range considered in this study (< 6 mo; Casale et al 2009a), have been found stranded along the Ionian-south Adriatic coasts of Italy (Casale et Table 3. Results of the simulation of the dispersal of drifting particles from loggerhead and green sea turtle nesting areas to marine zones of the eastern Mediterranean basin.…”
Section: Discussion the First 'Lost Year' Of Mediterranean Sea Turtlesmentioning
confidence: 99%
See 2 more Smart Citations
“…The second important area for loggerhead hatchlings appears to be the Ionian-south Adriatic. Accordingly, turtles of the size range (<10 cm), corresponding approximately to the age range considered in this study (< 6 mo; Casale et al 2009a), have been found stranded along the Ionian-south Adriatic coasts of Italy (Casale et Table 3. Results of the simulation of the dispersal of drifting particles from loggerhead and green sea turtle nesting areas to marine zones of the eastern Mediterranean basin.…”
Section: Discussion the First 'Lost Year' Of Mediterranean Sea Turtlesmentioning
confidence: 99%
“…4 to 6 mo after release. Loggerheads of about 6 mo in age have a CCL of about 10 cm length (Casale et al 2009a), and it is likely that passive drift is no longer the only form of movement; hence particle tracking may be less useful to infer dispersal at this point. However, other studies carried out passive drifting simulations for 1 yr or more (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was similar to an ATM using capture-mark-recapture (CMR) and skeletochronology in headstarted Kemp's (10-17 years; Snover et al, 2007), but longer than an estimate from captive animals (5-12 years; Bjorndal et al, 2014), suggesting that growth and maturity may differ in the wild. Skeletochronology has also shed light on ATM in green, loggerhead, and leatherback turtles (Avens et al, 2009;Turner Tomaszewicz et al, 2015), as have a small number of direct observational studies from headstarted turtles (e.g., Florida and Caribbean green turtles, Keske et al (2016) and Bell et al (2005), respectively), CMR via carapace punches in South African loggerheads (Tucek et al, 2014) or growth rates (Casale et al, 2009). The general consensus emerging from these studies, is that each species and perhaps each population may have different ATM ranges.…”
Section: Life Historymentioning
confidence: 99%
“…1). Moreover, the southern Adriatic and to a lesser extent the northern Adriatic and Ionian sea are important developmental areas for loggerheads in the first four years of their lives (Casale et al 2009). Preferred loggerhead habitats off the Spanish Mediterranean coast are characterized by a large number of juveniles, especially around the Balearic islands during spring and summer (Camiñas and de la Serna 1995) and around Columbretes Island Marine Reserve throughout the year (Gómez de Segura et al 2003).…”
Section: Sea Turtle Distributionmentioning
confidence: 99%